2014
DOI: 10.1209/0295-5075/108/27004
|View full text |Cite
|
Sign up to set email alerts
|

Angle dependence of the photonic enhancement of the magneto-optical Kerr effect in DMS layers

Abstract: We investigate theoretically an angle dependence of enhancement of polar magneto-optical Kerr effect (MOKE) obtained thanks to a deposition of a paramagnetic Diluted Magnetic Semiconductor (DMS) layer on one-dimensional photonic crystal layer. Our transfer matrix method based calculations conducted for TE and TM polarizations of the incident light predict up to an order of magnitude stronger MOKE for a (Ga,Fe)N DMS layer when implementing the proposed design.The maximum enhancement for TE and TM polarization o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Another type of material is a semiconductor system relatively resistant to manganese induced optical degradation: Cd 1−x Mn x Te, which was already used as a high refractive index layer in microcavities with Cd 1−x Mn x Te quantum wells 24,25 . Indeed such a system exhibits strong magneto-optical properties [26][27][28] related to the shift of both exciton and photon states 24,29 , therefore it can be used for tuning the exciton-photon energy difference and for tuning the Rabi oscillation frequency [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…Another type of material is a semiconductor system relatively resistant to manganese induced optical degradation: Cd 1−x Mn x Te, which was already used as a high refractive index layer in microcavities with Cd 1−x Mn x Te quantum wells 24,25 . Indeed such a system exhibits strong magneto-optical properties [26][27][28] related to the shift of both exciton and photon states 24,29 , therefore it can be used for tuning the exciton-photon energy difference and for tuning the Rabi oscillation frequency [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the magneto-optical Kerr effect can be amplified by placing a DMS layer on a distributed Bragg reflector. [6][7][8][9][10][11] Magneto-optical effects of cavity polaritons can be enhanced by embedding quantum wells containing Mn ions in the cavity. [12][13][14][15][16][17][18][19] The structure of the microcavity sample studied in this work is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Such a mechanism has been discussed to enhance the MOKE in Fe/Cu bilayers 33 . The photonic effect can also be used to enhance the MOKE because of multiple interference of light within the magnetic multilayers [34][35][36] . Cavity enhancement of the MOKE has also been reported, in which a dielectric layer acts as a Fabry-Perot optical cavity [37][38][39] .…”
Section: Introductionmentioning
confidence: 99%